Defensive Lines in System of Russian Settlement in Tobol-Ishim Interfluve at End of 16th — Middle of 18th Centuries - V. A. Zakh (Научный диалог)
The formation of defensive lines in the Tobol-Ishim interfluve, which marked the advance of the Russian population to the south, is considered. It is proved that the historical processes that took place in Tobolo-Ishimye, the construction of defensive lines, along with the inclusion of existing communications, should be considered as the formation of a structure for the settlement of the Russian and Tatar population in the process of colonization with the advance of the border of the Russian state to the south. The initial line of colonization was formed at the end of the 16th century from the first Russian prisons: Turin, Tyumen and Tobolsk, which laid the foundation for the development of the forest-steppe lands of Tobol-Ishim. The intermediate lines were P. I. Godunov’s “notch line”, which stretched from the Tarkhansky prison to the Kataisky prison, and the Ishim defensive line — from the Utyatsky outpost to the Omsk fortress. The last defensive line ran directly from the Zverinogolovsky tract through the fortress of St. Peter to Omsk, included fortresses, redoubts and lighthouses that protected the territories of the Trans-Urals and the south of Western Siberia from the raids of the Jungars and nomads of the Middle Kazakh horde. Defensive lines with dotted centers of territory development, along with roads and waterways, fastened the emerging initial framework of Russian settlement in Tobolo-Ishimye with the center in Tobolsk.